Regional development gaps in Argentina: A multidimensional approach to identify the location of policy priorities - Niembro, Andrés Alberto (2020)
Fil: Niembro, Andrés A. Universidad Nacional de Río Negro. Centro Interdisciplinario de Estudios sobre Territorio, Economía y Sociedad (CIETES). Río Negro, Argentina.